(3eNJUQ cJGH GdadGMIs - (3bSWhS Hf GSchO GScjfIs ((3CHh fUQ gHI Gddg Hf jMji Hf gHI Gddg Hf LHQjd GdfUQGfi s)
(3ChdgG (B:s
(3GdHGH GdChd ai eYQaI GdghGA GdUGai GdUMjM aEfg UaGA GdLh hUMJg jchf eY Pdc ef QbI GdbeQ hUaGJg s
(3BNQgG (B:s
(3GdHGH GdMGOi hGdKdGKhf ajeG jSJYjf Hg WGdH GdMGLI Ydi GdfLGM gi QbjI JQcfGgG Ydi YeO Je cJGH GdadGMjf s
(3Jdjg UaI GdeOGO hUaI LdH GdPgH hGdaVIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1447s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdRQGYI h GdCYTGHs